PROGRAM RESOLVED ADDITIVE PROBLEMS TO IMPROVE PROBLEM RESOLUTION CAPABILITIES IN THE PRIMARY STUDENTS OF THE MASISEA DISTRICT - Vasquez Galan, Manuel Pedro (2020)
The “I Solve Additive Problems Program toimprove problem-solving capabilities in the students ofthe second grade of primary education of the educationalinstitutions of the Masisea district, Ucayali Region, 2015”is experimental and aimed to determine to what extent theProgram Solving additive problems improves the problemsolving capabilities of the students in the sample, by virtueof which a set of learning sessions was developed, withexercises linked to the school environment. The designwas quasi-experimental, the population of 138 studentsand the sample of 28 students in the experimental groupand 20 in the control group, being the non-probabilisticsampling, the instrument used was a pedagogical problem-solving test of 20 reagents, the which wasvalidated by expert judgment and to which Cronbach’salpha reliability analysis was applied, whose result was0.70. The result was that the experimental group achievedthat 57.1% of children were located at the expected levelof achievement, exceeding that of control notoriously, inaddition the student’s hypothesis test gave a sig. = 0.00; itis concluded that the Program Solving additive problemsdoes substantially improve problem-solving capabilities inthe school population of the Masisea district, Ucayali.